LEKSIKON PERALATAN RUMAH TANGGA TRADISONAL DALAM BAHASA DAYAK SALAKO - Yeprarini, Yeprarini; Simanjuntak, Hotma; Muzammil, Ahmad Rabi'ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research was motivated by the interest in Dayak Salako culture, especially about traditional household appliances which are currently rarely used by the community. The issues studied are regarding the form, meaning, and implementation of Indonesian learning about the lexicon of traditional household appliances in the Salako Dayak language. The method used is a descriptive method with a form of qualitative research. The data collection techniques used are observation, interview, listen, record and record, and documentation techniques. This research produced 46 lexicons of traditional household appliances in Dayak Salako language consisting of 9 household utensils made of wood, 29 made of iron, 2 made of clay / ceramics, and 1 made of thorny pandan leaves. The lexicon form of traditional household appliances in Dayak Salako language is monomorphemic totaling 34 lexicons, polymorphemic 2 lexicons, and phrases 10 lexicons. The meanings in the lexicon of traditional household appliances were analyzed based on the lexical meaning of 37 lexicons, the grammatical meaning of 9 lexicons, and the cultural meaning of 4 lexicons. The supplementary form of Indonesian learning text is in the form of a description text on the lexicon of traditional household appliances in the Salako Dayak language.